Astrocytes Downregulate Inflammation in Lipopolysaccharide-Induced Acute Respiratory Distress Syndrome: Applicability to COVID-19 - Izrael, Michal; Molakandov, Kfir; Revel, Ariel; Slutsky, Shalom Guy; Sonnenfeld, Tehila; Weiss, Julia Miriam; Revel, Michel (Frontiers in Medicine, 2021)
Background: An acute respiratory distress syndrome (ARDS) is caused by the increased amounts of pro-inflammatory cytokines and neutrophil-mediated tissue injury. To date, there is no effective treatment for the ARDS available, while the need for one is growing due to the most severe complications of the current coronavirus disease-2019 (COVID-19) pandemic. The human astrocytes (AstroRx) have shown immunomodulatory properties in the central nervous system (CNS). This study aimed to evaluate the capacity of astrocytes to decrease lung inflammation and to be applied as a treatment therapy in ARDS. Methods: First, we assessed the ability of clinical-grade AstroRx to suppress T-cell proliferation in a mixed lymphocyte reaction test. Next, we tested the therapeutical potential of AstroRx cells in a lipopolysaccharide (LPS)-based ARDS mouse model by injecting AstroRx intravenously (i.v). We determined the degree of lung injury by using a severity scoring scale of 0–2, based on the American Thoracic Society. The scoring measured the presence of neutrophils, fibrin deposits, and the thickening of alveolar walls. The state of inflammation was further assessed by quantifying the immune-cell infiltration to the bronchoalveolar lavage fluid (BALF) and by the presence of proinflammatory cytokines and chemokines in the BALF and serum. Results: We detected that AstroRx cells were capable to suppress T-cell proliferation in vitro after exposure to the mitogen concanavalin A (ConA). In vivo, AstroRx cells were able to lower the degree of lung injury in LPS-treated animals compared with the sham injected animals (P = 0.039). In this study, 30% of AstroRx treated mice showed no lung lesions (responder mice), these mice presented a steady number of eosinophils, T cells, and neutrophils comparable with the level of naïve control mice. The inflammatory cytokines and chemokines, such as TNFα, IL1b, IL-6, and CXCL1, were also kept in check in responder AstroRx-treated mice and were not upregulated as in the sham-injected mice (P < 0.05). As a result, the LPS-treated ARDS mice had a higher survival rate when they were treated with AstroRx. Conclusions: Our results demonstrate that the immunosuppressive activity of AstroRx cells support the application of AstroRx cells as a cell therapy treatment for ARDS. The immunoregulatory activity may also be a part of the mechanism of action of AstroRx reported in the amyotrophic lateral sclerosis (ALS) neurodegenerative disease.